PENERAPAN PENDEKATAN SAINTIFIK OLEH GURU PADA PEMBELAJARAN SOSIOLOGI DI SMA SEKECAMATAN SUNGAI AMBAWANG - Novelina, Radha; Zakso, Amrazi; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to study the application of scientific approaches by teachers in the study of sociology at high school in the sub district of Sungai Ambawang. The form of research used is quantitative with a descriptive approach. The population in this study were all sociology teachers in high school in Sungai Ambawang sub-district, which is 3 schools. The sample used is three sociology teachers who have implemented the 2013 curriculum with a scientific approach. Data collection tools in the form of questionnaires, notebooks and archives. The data that the researchers used were processed using SPSS 20.0 non-parametric binomial test, which is used to test the hypothesis of a proportion of the population consisting of class groups. The binomial test will compare the observed frequency of the category in a dichotomous variable to the expectation frequency under binomial distribution with certain probability parameters. Data analysis uses percentages. The results prove that Ha was approved by the Application of the Scientific Approach by Teachers in Sociology in the high school, Sungai Ambawang sub-district has been set at 60% or included in the category enough. Keywords: Scientific Approach, Teacher, Sociology Learning